Ferroelectric and piezoelectric properties of bismuth titanate thin films grown on different bottom electrodes by soft chemical solution and microwave annealing - Simoes, A. Z.; Cruz, M. P.; Ries, A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Ramesh, R. (Elsevier B.V., 2007)
Bismuth titanate (Bi4Ti3O12, BIT) films were evaluated for use as lead-free piezoelectric thin films in micro-electromechanical systems. The films were grown by the polymeric precursor method on LaNiO3/SiO2/Si (1 0 0) (LNO), RuO2/SiO2/Si (1 0 0) (RuO2) and Pt/Ti/SiO2/Si (1 0 0) (Pt) bottom electrodes in a microwave furnace at 700 degrees C for 10 min. The domain structure was investigated by piezoresponse force microscopy (PFM). Although the converse piezoelectric coefficient, d(33), regardless of bottom electrode is around (similar to 40 pm/V), those over RuO2 and LNO exhibit better ferroelectric properties, higher remanent polarization (15 and 10 mu C/cm(2)), lower drive voltages (2.6 and 1.3 V) and are fatigue-free. The experimental results demonstrated that the combination of the polymeric precursor method assisted with a microwave furnace is a promising technique to obtain films with good qualities for applications in ferroelectric and piezoelectric devices. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: thin films; chemical synthesis; ferroelectricity